SIX1 Activates STAT3 Signaling to Promote the Proliferation of Thyroid Carcinoma via EYA1 - Kong, Deguang; Li, Anping; Liu, Yu; Cui, Qiuxia; Wang, Kun; Zhang, Dan; Tang, Jianing; Du, Yaying; Liu, Zhisu; Wu, Gaosong; Wu, Kongming (Frontiers in Oncology, 2019)
As a critical member of the Retinal Determination Gene Network (RDGN), SIX1 has been regarded as a tumor promoter in various types of cancer. However, its role in papillary thyroid carcinoma (PTC) has never been investigated. In this study, thyroid carcinoma tissue microarray staining was employed to identify the expression patterns of SIX1 and its co-activator EYA1. Papillary thyroid cancer cell lines, BCPAP, and TPC-1 cells were used to investigate the potential mechanism of SIX1 in vitro and in vivo. Flow cytometry analysis, MTT assay, the growth curve assay, colony formation assay, EdU incorporation and xenograft assay were performed to demonstrate the role of SIX1 in the malignant change of PTC cells. Western blot and Real-time PCR were used to detect the interaction among the SIX1, EYA1, and STAT3 signaling. In comparison with normal tissue, high expressions of SIX1 and EYA1 were associated with a malignant tumor. Importantly, SIX1 strongly correlated with EYA1 in thyroid carcinoma tissue microarray. Functional assays indicated SIX1 increased EYA1 expression by stabilizing EYA1 at the post-transcriptional level. Besides, SIX1 promoted the proliferation and invasion of thyroid carcinoma via activation of STAT3 signaling and its downstream targets in an EYA1-dependent manner. SIX1 can integrate with EYA1 to contribute to PTC development via activation of the classical STAT3 signaling. These data suggested targeting the abnormal activation of the SIX1/EYA1 complex may represent a novel therapeutic strategy for advanced PTC patients.